2018
DOI: 10.1002/ceat.201700522
|View full text |Cite
|
Sign up to set email alerts
|

Collision Characteristics for Predicting Particle Attrition and Pipe Wear in Conveying Systems

Abstract: Pipe wear and particle attrition are common and undesired effects when conveying particles in pipelines. An approach for predicting these effects to spare considerable efforts spent in trial and error to achieve the optimum operating conditions is reported. The model is composed of a one‐dimensional flow model that calculates the two‐phase flow dynamics, a one‐dimensional breakage algorithm (ODBA) to compute attrition of the particles, and a one‐dimensional erosion model (ODEM) to compute the erosion rate. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Peng and Cao [ 27 ] investigated elbow erosion for multiphase flow and found that maximum erosion occurs adjacent to outlet due to the cumulative effect of sliding and direct impaction. Uzi et al [ 28 ] scrutinized the particle wall interaction of the elbow pipe and concluded that the maximum particle wall collation was at 53° along the curvature despite the particle size. Mansouri et al [ 29 ] investigated numerically and experimentally the erosive wear of elbows configurations for quartz particles.…”
Section: Introductionmentioning
confidence: 99%
“…Peng and Cao [ 27 ] investigated elbow erosion for multiphase flow and found that maximum erosion occurs adjacent to outlet due to the cumulative effect of sliding and direct impaction. Uzi et al [ 28 ] scrutinized the particle wall interaction of the elbow pipe and concluded that the maximum particle wall collation was at 53° along the curvature despite the particle size. Mansouri et al [ 29 ] investigated numerically and experimentally the erosive wear of elbows configurations for quartz particles.…”
Section: Introductionmentioning
confidence: 99%